Does Smoking Reduce the Progression of Osteoarthritis? Meta‐Analysis of Observational Studies. Issue 7 (1st July 2013) - Pearce, Fiona; Hui, Michelle; Ding, Changhai; Doherty, Michael; Zhang, Weiya
<x xml:space="preserve">Abstract</x> Objective To determine whether smoking reduces the progression of osteoarthritis (OA). Methods Observational studies examining smoking and progression of OA were systematically searched through Medline (1948–), EMBase (1980–), Web of Science, PubMed, and Google and relevant references. The search was last updated in May 2012. Odds ratios (ORs) and 95% confidence intervals (95% CIs) were directly retrieved or calculated. Current standards for reporting meta‐analyses of observational studies (Meta‐Analysis of Observational Studies in Epidemiology) were followed. Quality‐related aspects such as study design, setting, sample selection, definition of progression, and confounding bias were recorded. Stratified and meta‐regression analyses were undertaken to examine the covariates. Results Sixteen studies (976, 564 participants) were identified from the literature. Overall, there was no significant association between smoking and progression of OA (OR 0.92; 95% CI 0.83, 1.02). There was moderate heterogeneity of results (I2 = 57.3%, P = 0.0024). Subgroup analyses showed some associations of marginal significance; however, meta‐regression did not confirm any significant results. Conclusion There is no compelling evidence that smoking has a protective effect on the progression of OA. The results concur with a previous meta‐analysis published by this group that showed no association between smoking and incidence of OA. Taken together, smoking does not appear to reduce either the incidence or progression of OA.